Endogenous business cycles and economic policy - Peter Skott (University of Massachusetts, Department of Economics, 2023)
This paper examines the dynamics of Keynesian models that incorporate feedback effects from the labor market to income distribution, investment, aggregate demand and output. A baseline version of the model can generate endogenous growth cycles, but cumulative divergence and economic collapse also become possible for plausible parameter values. Extensions of the model that include monetary and Öscal policy show greater robustness: the local instability of the stationary point leads to limit cycles (rather than complete collapse), even when large, destabilizing changes are made to parameters describing the private sector. The robustness of the general approach is reinforced by the endogeneity of the Öscal and monetary policy rules.
Keywords: E12; E32; E52; E62; 330; growth cycles; Harrodian instability; income distribution; Taylor rule; fiscal policy